2016
DOI: 10.1017/s0030605316000302
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and conservation status of the Endangered pepperbark tree Warburgia salutaris (Canellaceae) in Swaziland

Abstract: The Endangered Warburgia salutaris (Bertol. f.) Chiov. (Canellaceae), a sought-after medicinal plant in southern Africa, is on the verge of extinction as a result of overexploitation for illegal trade. As part of formulating a conservation strategy for the species in Swaziland we sought to determine its distribution and population status and to revise its national conservation status. Field surveys were conducted in all physiographic regions of Swaziland. Eighteen locations of species presence were found, of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…However, subsequent studies confined the distribution of W. salutaris to only a sub-region of southern Africa, i.e. South Africa 21,49 , Eswatini (previously known as Swaziland) 24,50 , Zimbabwe 29,[51][52][53] , Malawi 54 and Mozambique 55 . This species is commonly used to treat several ailments such as common colds, throat and mouth sores, or coughs 47,48 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, subsequent studies confined the distribution of W. salutaris to only a sub-region of southern Africa, i.e. South Africa 21,49 , Eswatini (previously known as Swaziland) 24,50 , Zimbabwe 29,[51][52][53] , Malawi 54 and Mozambique 55 . This species is commonly used to treat several ailments such as common colds, throat and mouth sores, or coughs 47,48 .…”
mentioning
confidence: 99%
“…However, with commercial demand increasing, W. salutaris groves were repeatedly raided by harvesters that often debarked the whole tree, especially mature plants 56 . Severe harvesting resulted in high tree mortality in many areas and in the extinction of many local populations 21,24,57 and consequently, W. salutaris is considered threatened throughout its range 50,58,59 , and listed as an Endangered Species in the IUCN Red List 57 . The most extreme case is that of Zimbabwe, where the species is listed as extinct in the wild 29,60 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chiov.) is more dramatic, as this medicinal plant has not only been classified as Endangered in Swaziland (Dludlu et al, 2017), but its population is steadily shrinking due to illegal trading and uncontrollable harvesting. Its increasing popularity as a traditional medicine contributed to its overexploitation, resulting in its classification as Extinct in the Wild in Zimbabwe (Botha et al, 2004; Dludlu et al, 2017).…”
Section: Case Study 2: Sustainable Sourcingmentioning
confidence: 99%
“…Its growth habitat is forests and kloofs. Dludlu et al (2017) reported eighteen localities where Warburgia salutaris is found in Eswatini, across a wide range of habitats, physiographic zones, geology, and vegetation type. The Warburgia salutaris plant (Figure 1) is listed as endangered in the International Union of Conservation of Nature (IUCN) red data list and as critically endangered in the Swaziland National Trust Commission (SNTC) (2016) list.…”
Section: Some Important Medicinal Plants In Eswatinimentioning
confidence: 99%